The effect of additives on the quality of white lupin–wheat silage assessed by fermentation pattern and qPCR quantification of clostridia - König, W.; Lamminen, M.; Weiss, K.; Tuomivirta, Tero T.; Sanz Munoz, S.; Fritze, Hannu; Elo, K.; Puhakka, L.; Vanhatalo, A.; Jaakkola, S. (Wiley, 2017)
The efficacy of different silage additives on different mixtures of white lupin and spring wheat was investigated in four separate trials. The bicrop was harvested 96 days (trials 1 and 2) and 110 days (trials 3 and 4) after sowing. For each maturity stage, two mixtures of white lupin and spring wheat were reformed in the ratios of 1:2 and 2:1 on fresh matter (FM) basis respectively. The crops were treated with formic acid (FA), sodium nitrite–hexamine mixture (NaHe) or homofermentative lactic acid bacteria (LAB). The control silage was made without additive. Additives were not able to improve the quality of white lupin–wheat silage in all trials, compared with untreated silage. The treatment with LAB showed good results only at the first stage of crop maturity with sufficient amounts of water-soluble carbohydrate in the pre-ensiling crops. The FA treatment showed elevated butyric acid levels in all trials, which suggests that the FA application level used (4 L t 1 FM, 100% FA) was insufficient to decrease pH enough for preventing the growth of clostridia and butyric acid fermentation. NaHe was the only additive that was able to inhibit the activity of clostridia in all trials.
Keywords: bicrop; clostridia; qPCR; white lupin; additives; silage